Psychological distress is associated with symptoms of post-traumatic stress disorder among healthcare providers during the COVID-19 pandemic: 2021–2023 - Coleman, Brenda L.; Gutmanis, Iris; Maunder, Robert; McGeer, Allison (Frontiers in Psychology, 2025)
BackgroundDuring the COVID-19 pandemic, approximately 25% of healthcare providers (HCP) worldwide were reported to have experienced symptoms associated with post-traumatic stress disorder (PTSD). While longitudinal studies have identified factors associated with PTSD in this group of essential workers, associations with psychological distress trajectories have not been studied.MethodsHealthcare providers who participated in the prospective Canadian COVID-19 Cohort Study were eligible. Baseline data were collected at enrolment with time-varying measures updated by participants every 12 months. Kessler Psychological Distress Scale (K10) questionnaires were completed in March 2021 or upon their recruitment (whichever came first) and every 6 months thereafter. Impact of Event Scale-Revised (IES-R) questionnaires were completed within two weeks of their withdrawal from the study or study termination date (December 2023). Modified Poisson regression was used to assess the association between PTSD symptoms (i.e., IES-R scores of < 24 vs. ≥ 24) and score trajectories of the first four K10 questionnaires that were completed 180 (± 60) days apart.ResultsOf 441 participants, 105 (24.0%) had IES-R scores indicative of concern for PTSD (i.e., ≥ 24). Five trajectories of K10 scores were identified including: resilient (n = 111, 25.2%), chronically distressed (131, 29.7%), delayed onset of distress (43, 9.8%), recovery (83, 18.8%), and mutable (73, 16.6%). HCP whose K10 score trajectories were classified as chronically distressed (i.e., all ≥ 16) had rates of IES-R scores indicative of PTSD that were 6.9 times [95% confidence interval (CI) 3.7, 13.0] higher than HCP with resilient score trajectories (i.e., all < 16). Participants with scores in the other three K10 trajectories also had higher rates of IES-R scores of ≥ 24 when compared to those with resilient scores, with adjusted incident rate ratios of 2.6 (delayed onset; CI 1.3, 5.1), 3.1 (recovery; CI 1.4, 7.2), and 4.0 (mutable; CI 2.2, 7.3).ConclusionEarly and repeated assessment of HCP distress levels will help identify those who are distressed so that evidence-based mitigation strategies can be provided.